Two-way Quantum Key Distribution Under Fully Measurement-Device-Independent Assumption - Liu, Jie; Zhang, Ting; Wu, Xiao Lu; Kang, Guo-Dong (European Journal of Applied Sciences, 2022)
In this paper, we prove the security of the LM05’s two-way quantum key distribution (TWQKD) under the assumption that detector devices in both Alice’s and Bob’s sides are controlled by eavesdroppers. Using a relatively simple method, more practical, we give an analytical proof that LM05’s TWQKD is measurement-device-independent (MDI) security in both the quantum forward channel and the quantum backward channel. This is the first work shows that TWQKD has fully MDI characteristic, thus makes it immune to all possible detector-device-attacks in two-quantum-way in actual implementations.